How to strengthen non-motorised mobility of elderly people? An evidence-based manual for the set-up of fall prevention programmes in communities. - Eichhorn, Anita; Aigner-Breuss, Eva (My University, 2017)
Beschrieben werden die Aktivitäten des Kuratoriums für Verkehrssicherheit (KFV) im Bereich Sturzprophylaxe zum Erhalt der Mobilität älterer Menschen. Das KFV richtet sich dabei an die Kommunen und gibt Anregungen, wie Gemeinden Mobilitätsangebote für ältere Menschen zielgerichtet bereit stellen können.

In the course of life, mobility behaviour and needs change and have to be adapted. With growing age, muscle mass reduces continuously. If this natural degradation process is not countered, the risk of falls and getting injured increases. Once a person has experienced a fall, the fear of falling again is likely to evolve. As a consequence, physical activity is associated with feelings of insecurity and is therefore avoided (post-fallsyndrome). Within the age group 55 years and older, almost a quarter of occurring falls in Austria happen in traffic (KFV, 2016). Thus, motivity and health are key prerequisites for a safe, independent and injury-free mobility. In order to tackle this topic, the Austrian Road Safety Board (Kuratorium für Verkehrssicherheit, KFV) developed the project "Pimp your Skills" (Eichhorn et al., 2016), which focused on strengthening non-motorised mobility of elderly people and, particularly, on fall prevention. As a result, a manual on setting up an effective fall prevention programme for adults is now available.
Keywords: Gemeinde; Alter Mensch; Fußgängerverkehr; Mobilität; Gesundheitsvorsorge; Förderungsprogramm; Sturzprophylaxe; Bewegungsförderung